A Review of Taína: Una novela - Gaffney Samuels, Justin (The Grove - Working Papers on English Studies, 2021)
Taina: Una Novela makes strong statements about how social justice, individual determination, education, and compassion can overcome urban poverty. The main character, Julio is a half Ecuadorian/half Puerto Rican teenager who was born and raised in East Harlem. He has good grades and aspires to get into Princeton University. Julio gets the support he needs for his future from his parents and a couple of good teachers from his school. Clearly, Quiñonez makes an important statement as an educator on the things that are needed to deal with issues of urban poverty. Julio ends up believing Taina, a girl marginalized by the whole neighborhood, has an immaculate pregnancy. Taina and her mother are poor, and Julio does criminal acts to support her and her mother. Quiñonez explores the effects of marginalization on mental health, as Taina and her mother become crude, hostile people in their isolation from society.